Efektivitas Kebijakan Moneter di Indonesia - Suhendri; Satria, Doni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to analyze the effectiveness of monetary policy in Indonesia. This study uses the VECM method and shows that monetary policy, through interest rates and money supply, effectively manages inflation, economic growth, and exchange rates in the long run, despite variations in the short-run impact. These results suggest a lag in the transmission of monetary policy and emphasize that the Indonesian economy is heavily influenced by external factors, such as world oil prices and economic growth in developed countries. Rising oil prices depress the rupiah exchange rate and increase inflation, while growth in advanced economies supports rupiah stability. An increase in interest rates and money supply also strengthens the exchange rate, as per Mundell-Fleming theory, making monetary policy an effective tool for macroeconomic stability.